Universal Health Coverage for Inclusive and Sustainable Development : Country Summary Report for Thailand - Patcharanarumol, Walaiporn; Tangcharoensathien, Viroj; Wibulpolprasert, Suwit; Suthiwisesak, Peerapol (World Bank Group, Washington, DC, 2014)
Thailand, an upper-middle-income country with a population of 69.5 million in 2012, achieved its health-related Millennium Development Goals by the early 2000s. The health care delivery system has received significant investments in the past three or four decades and now offers extensive health infrastructure coverage that reaches even the most rural and remote areas, in a publicly dominated health system. However, ensuring equity among the three main public insurance programs and assuring fiscal sustainability are the major challenges facing the current system.